Investigating verb-noun lexical collocational errors in a Malaysian english learner corpus - Ang, Leng Hong (2010)
This study employed a corpus-based method to investigate types and sources of verb-noun lexical collocational errors in a subcorpus of a Malaysian learner corpus, EMAS (The English ofMalaysian School Students). The corpus consists of a total of 130 essays written by Form Four Malay learners from three different states in peninsula Malaysia. The study adopted Howarth's (1998) definition which states that collocations are word combinations which include free combinations and restricted collocations. Although there are two categories of collocations, namely lexical and grammatical collocations (Benson, Benson and Ilson, 1986), this study only investigated one type of lexical collocation, which is verb-noun lexical collocations. Nevertheless, following Nesselbauf's framework for classification of types of collocational errors, the investigation of verb-noun lexical collocations in this study includes grammatical elements which occur in the collocations, such as prepositions. The term verb-noun lexical collocations in this study was redefined as combinations of a verb and a noun which take into account grammatical elements such as prepositions.